The synthesis of TiAlN composites by condensation of the different arc plasma flows - Taran, V.S.; Tereshin, V.I.; Timoshenko, A.I.; Chechel’nitskij, O.G.; Kryshtal’, A.P. (Вопросы атомной науки и техники, 2005)
Some properties of the arc-vapour deposited TiAlN films, obtained both – by condensation of the different and combined titanium and aluminium plasma flows, have been investigated. The different flows was provided by two arc evaporators with titanium and aluminium cathodes, at that, the aluminium plasma was passed through the curvilinear plasma filter. The combined titanium-aluminium plasma was generated by single evaporator with the alloyed TiAl cathodes, which have a volumetric content of aluminium 50 %. The growth rates, surface morphology and the Vickers hardness of the TiAlN films, obtained under the various conditions, have been analyzed. The comparative cutting tool trials with the cemented carbide drills, covered by TiN, TiCN and TiAlN were conducted. It is shown, that the TiAlN film compositions, condensed from different plasma flows with the filtering aluminium plasma, are more profitable and has much higher characteristics, than films, obtained from alloyed TiAl cathodes.